Assessment of circulating proteasome chymotrypsin-like activity in plasma of patients with acute and chronic leukemias - Ostrowska, Halina; Hempel, Dominika; Holub, Malgorzata; Sokolowski, Jaroslaw; Kloczko, Janusz (Clinical biochemistry, 2008)
We evaluated whether the proteasomal chymotrypsin-like (ChT-L) activity is increased in plasma of patients with acute lymphoblastic (ALL), acute myeloblastic (AML) and chronic lymphocytic (CLL) leukemias. The activity was assayed using the fluorogenic peptide substrate in the presence of an artificial activator sodium dodecyl sulfate (SDS) in the plasma of healthy donors ( n = 15) and ALL ( n = 15), AML ( n = 28) and CLL ( n = 22) patients. The activity was significantly ( P < 0.001) higher in the plasma of ALL and AML patients at the diagnosis than in healthy subjects and decreased after therapy or remained unchanged or rose during relapse. By contrast, in CLL patients at the diagnosis, the activity did not differ significantly from the healthy controls. In each group, the activity positively correlated with the serum lactic dehydrogenase activity. Plasma proteasome ChT-L activity can be a useful bio-marker for patients with acute leukemia at the blast stage.